2022
DOI: 10.1108/jd-08-2021-0148
|View full text |Cite
|
Sign up to set email alerts
|

Volunteers' strategies for supporting asylum seekers with information challenges

Abstract: PurposeThis paper examines the strategies that volunteers use when supporting asylum seekers with their information challenges to be able to develop services for asylum seekers and promote their access to reliable information in the most suitable way.Design/methodology/approachSemi-structured interviews were conducted with seven volunteers who help asylum seekers with their asylum cases in two cities in Finland. The interview data was thematically coded and analysed.FindingsSix types of information-related str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…FAR and SR provide leaflets, posters, artistic materials, and ideas that others can use. In the uncertain and complex situations information mediators have to balance the amount and quality of information they give to others (Ruokolainen, 2022). The Russian resistance projects use the straightforward and simple language and minimize the use of external sources in their communication to avoid the complexities of information contexts and the dangers of direct attribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FAR and SR provide leaflets, posters, artistic materials, and ideas that others can use. In the uncertain and complex situations information mediators have to balance the amount and quality of information they give to others (Ruokolainen, 2022). The Russian resistance projects use the straightforward and simple language and minimize the use of external sources in their communication to avoid the complexities of information contexts and the dangers of direct attribution.…”
Section: Resultsmentioning
confidence: 99%
“…Information practices are embedded in the social practices, and in the context of new, unusual, or challenging circumstances they can be seen as the processes of learning and adaption (Ruokolainen, 2022; Savolainen, 2007). With the start of the invasion, those who could not stay away and remain impassionate observers began using their status and skills to enter the public sphere and gather and disseminate information, help others in using linguistic and extralinguistic resources, and offer support, information resources, and inspiration, hoping that their actions would lead to change.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…Earlier studies have identified that this role is primarily undertaken by information professionals, volunteers, nurses, social care workers and family members (Buchanan et al. , 2019; Ruokolainen, 2022), while a common assumption is that information intermediaries tend to have relatively strong language literacy skills and educational background and that they are well regarded by their communities (Seale et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Information intermediaries are described as an important source of information, who they can support information needs recognition as well as tailor information to the particular needs of the other, especially in disadvantaged contexts (Buchanan et al, 2019). Earlier studies have identified that this role is primarily undertaken by information professionals, volunteers, nurses, social care workers, and family members (Buchanan et al, 2019;Ruokolainen, 2022), while a common assumption is that information intermediaries tend to have relatively strong language literacy skills and educational background and that they are well regarded by their communities (Seale et al, 2022). In our study we extend this understanding and show that information intermediaries can also be one's peers who can enable them to begin understanding what information they need (e.g., information on how to protect against transmission following diagnosis) by further contextualising this drawing from their own experiences (e.g., preparing nutritional meals for the cared for person when resources are scarce).…”
Section: Theoretical Contributionsmentioning
confidence: 99%